Analisis Pengetahuan dan Tindakan Pencegahan Demam Berdarah Dengue (DBD) pada Masyarakat Pesisir di Lingkungan 16 Desa Cinta Damai Percut - Nurhayati Nurhayati; Faradillah Faradillah; Syahrida Suryani Hasibuan; Ayunda Sintia; Wafiq Azizah; Alditya Alfareza (Universitas Batanghari Jambi, 2023)
Dengue Hemorrhagic Fever (DHF) is a disease that has serious health impacts in various coastal areas. This study aims to analyze the prevention of DHF carried out by the coastal community in Cinta Damai Village, Percut Sei District in order to reduce the incidence and impact caused by this disease. This study used the interview method with a total of 10 respondents. The results of this study are that the coastal community of Cinta Damai Village already knows about DHF and its preventive measures. However, there are still coastal communities who have not applied this knowledge in their daily lives. This is indicated by the presence of dengue cases that attack them.